Тайна тринадцати апостолов - Александрова Наталья Николаевна (Артефакт & Детектив, 2018)
Экземпляры: ф.9 (20180906) / Инвентарный номер: 50391 / Цена: 95.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 46 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44